Recent Advances in Molecular Spintronics: Multifunctional Spintronic Devices. Issue 45 (25th January 2019) - Guo, Lidan; Gu, Xianrong; Zhu, Xiangwei; Sun, Xiangnan
Abstract: The field of spintronics has triggered an enormous revolution in information storage since the first observation of giant magnetoresistance (GMR). Molecular semiconductors are characterized by having very long spin relaxation times up to milliseconds, and are thus widely considered to hold immense potential for spintronic applications. Along with the development of molecular spintronics, it is clear that the study of multipurpose spintronic devices has gradually grown into a new research and development direction. The abundant photoelectric properties of molecular semiconductors and the intriguing functionality of the spinterface, together with novel designs of device structures, have promoted the integration of multiple functions and different mechanisms into discrete spintronic devices. Here, according to the different relationships between the integrated mechanisms, multifunctional molecular spintronic devices containing parallel and interactive types are highlighted. This is followed by the introduction of pure‐spin‐current‐type molecular spintronic devices that have already demonstrated great potential for multifunction exploration. Finally, the challenges and outlook that make this field young and energetic are outlined. Abstract : Multifunctional molecular spintronic devices, integrated with both spin‐valve effects and abundant optical or electrical functions, have grown into a new research direction. In terms of different integrated mechanisms, parallel, interactive, as well as pure‐spin‐current‐type molecular spintronic devices are introduced. Current challenges and expectations are proposed to show a complete picture of this emerging research field.